PANUVEITIS AS A MANIFESTATION OF OCULAR SYPHILIS IN PATIENTS WITH HUMAN IMMUNODEFICIENCY VIRUS : A CASE SERIES: Poster Presentation - Case Series - Resident - SITI AISYAH; Angga Fajriansyah; Susi Heryati; Arief Akhdestira Mustaram; Patrioka Muslima; Elfa Ali Idrus (Majalah Oftalmologi Indonesia, 2023)
Introduction : Syphilis is a sexually transmitted disease caused by the spirochete bacterium Treponema pallidum. Syphilis can result in multiple organ involvement, including the eyes, and demonstrates various clinical findings. Ocular syphilis is an important cause of uveitis in the new era of co-infection with the human immunodeficiency virus (HIV). Case Illustration : Case 1: A 29-year-old male HIV-positive with 5 months of blurred vision, pain, and redness in left eye (LE) with skin rashes on the palms and foots (Figure 1). The visual acuity was 1/300 in LE, anterior segment showed flare cell (Figure 2). Fundus examination (Figure 3) revealed multiple exudative lesion of right eye (RE) and vitreus opacity of LE due to inflammation. VDRL and TPHA tests were positive. Case 2: 38-year-old male, HIV-positive and tuberculosis-positive, with 2 months of blurred vision,pain and redness in both eyes with skin rashes on the palms and foots (Figure 1). The visual acuity of the RE was 1/60 and 1,5/60 in the LE on the initial visit. Anterior segment eye examination revealed flare and cell (Figure 2). Fundus examination revealed (Figure 3) preretinal hemorrhage and exudate of both eyes. VDRL and TPHA testing were positive, CD4 count showed severe immunodeficiency. Discussion : This study depicts clinical features and outcomes of two cases of ocular syphilis with HIV co- infection. Poor visual outcome was associated with posterior segment-involving uveitis at presentation. Conclusion : An accurate diagnosis is crucial, treatment is adjusted according to the clinical stage. Comprehensive education is needed for patients and their families.